The Impact of the "Coding Girls" Program on High School Students' Educational Choices - Stefania Basiglio; Daniela Del Boca; Chiara D. Pronzato (Institute of Labor Economics (IZA), 2023)
This paper evaluates the impact of "Coding Girls", an educational enrichment program designed to address the underrepresentation of women and girls in the fields of science, technology, engineering, and math (STEM) in Italy by stimulating young female students' interest in programming and science and encouraging them to consider careers in STEM-related fields. Implemented in ten secondary schools in Turin (Italy) over the period 2019-2022, the Coding Girls program provided lab-based computer programming instruction as well as introductory talks on specific topics in STEM. The program was evaluated by randomized controlled trial. Our results show that Coding Girls had a significant and positive impact on male and female students' programming skills and on their awareness of gender differences in the workforce. However, it did not seem to affect girls' aspirations to pursue higher education in STEM-related disciplines. The gender stereotypes children are exposed to from a very young age tend to steer girls and young women to the humanities. This bias is deeply entrenched and difficult to modify.
Keywords: J16; I23; 330; gender; STEM; higher educational choice